An evaluation of the safety impacts of safe routes to school bicycle education programs - Rush, Kathryn (Kansas State University, 2014)
Studies have shown that, since the early 1980s, the prevalence of overweight children and youth in the U.S. has tripled from approximately five to 16 percent of the population. Simultaneously, fewer and fewer children have been walking and cycling to school. Children—especially those aged 10 to 15 years—have some of the highest per capita traffic-related bicycle fatality and injury rates. While bicycle organizations, states and communities across the country have developed a variety of education programs independently and cooperatively with the National Safe Routes to School program, there is a lack of evaluation of the impact on bicycle safety, of different programs in different contexts, and of whether educational interventions reduce the risk of crashes and injuries. This study evaluated the effectiveness of Safe Routes to School programs with in-school bicycle education at reducing the crash rate and improving the safety of children and youth cyclists. The causal-comparative research design utilized bicycle mode share data collected from the National Center for Safe Routes to School for five existing programs—Boulder Valley School District Safe Routes to School, Eugene-Springfield Safe Routes to School, Safe Routes Philly, Portland Safe Routes to School, and Marin County Safe Routes to School—and crash data before and after program implementation for those respective communities. The crash assessment revealed a decreasing trend in crashes involving children and youth cyclists around treatment schools in the Eugene, OR and Philadelphia, PA program study areas, and at the aggregate level across program areas; but, this trend was not statistically significant when compared to the change in crashes around control schools in a quasi-experimental analysis. Nevertheless, the increase in students cycling to and from school reported by all but one of the programs, and the increase in exposure to crash risk as a result, indicated that the Safe Routes to School programs did not cause a decrease in the safety of student cyclists. Additional rigorous evaluations are needed utilizing randomized controlled design to maximize the reliability of reported findings and to aid decisions about where to invest resources in community-based approaches to injury prevention for cyclists.
Keywords: Bicycle; Bicycle safety; Bicycle education; Safe routes to school; Transportation (0709)